Minding Nature: Gallagher and the Relevance of Phenomenology to Cognitive Science. Issue 2 (3rd April 2018) - Clavel Vázquez, María Jimena; Wheeler, Michael
Abstract: In 'Rethinking Nature: Phenomenology and a Non-reductionist Cognitive Science', Gallagher [2019 ] sets out to overcome resistance to the idea that phenomenology is relevant to cognitive science. He argues that the relevance in question may be secured if we rethink the concept of nature. For Gallagher, this transformed concept of nature—which is to be distinguished from the classic scientific conception of nature in that it embraces irreducible subjectivity—is already at work in some contemporary enactive phenomenological approaches to cognitive science. Following a summary of Gallagher's argument, we argue that this rethinking of nature is not necessary to secure the aim in question. We articulate two alternative ways of achieving the relevance of phenomenology to cognitive science. The first, which turns on a minimal notion of naturalism, leaves the classic scientific conception of nature intact. The second, which turns on a practice-based analysis of collaboration between phenomenology and cognitive science, leaves it open which concept of nature one should adopt. As we show, each of the proposals on the table (Gallagher's own and our two alternatives) comes at a cost. Which of the three proposals is the more attractive will depend on which cost one wants to pay.